HABIB HUSEIN JAFAR'S DIGITAL PREACHING AND STRENGTHENING THE RELIGIOUS CHARACTER OF MUSLIM YOUTH - Anggilika Rahmatullah; Muhammad K holil (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Social media has become a popular means of Islamic preaching among Muslim teenagers. One popular figure is Habib Husein Ja'far, known for his relaxed, humorous, and easy-to-understand style. This study aims to examine how Habib Husein Ja'far's digital Islamic preaching can strengthen the religious character of teenagers. Using content analysis of several of his Islamic preaching videos on YouTube, TikTok, and Instagram, the study found that Habib Ja'far's Islamic preaching messages instill the values of faith, morality, and tolerance in a light yet touching manner. Many teenagers felt more enthusiastic about worship and developed a more positive outlook on religion after watching his content. This demonstrates that digital Islamic preaching can be an effective tool in fostering the religious character of the younger generation.